2009
DOI: 10.1016/j.physbeh.2009.03.005
|View full text |Cite
|
Sign up to set email alerts
|

The passive coping Roman Low Avoidance rat, a non-obese rat model for insulin resistance

Abstract: The aim of the study was develop to an animal model that links coping style to insulin resistance. We hypothesized that the psychogenetically selected Roman Low Avoidance (RLA) rats may serve as such a model. To test this hypothesis, we submitted both RLA and Roman High avoidance (RHA) rats to a series of intravenous glucose tolerance tests (IVGTT). These IVGTT were followed by post mortem metabolic characterization of the selection lines. It was found that plasma insulin levels are markedly elevated in the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
24
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 42 publications
6
24
0
Order By: Relevance
“…Studies that used rat strains selected for unconditioned fear reported a hyperreactive HPA axis in rats with high anxiety-like behavior [26]. Furthermore, animals obtained and bred using conditioned fear paradigms exhibit elevations in basal serum corticosterone levels and high emotionality [6,18]. In humans, individuals with anxiety disorders have high serum glucocorticoid levels [30,44].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies that used rat strains selected for unconditioned fear reported a hyperreactive HPA axis in rats with high anxiety-like behavior [26]. Furthermore, animals obtained and bred using conditioned fear paradigms exhibit elevations in basal serum corticosterone levels and high emotionality [6,18]. In humans, individuals with anxiety disorders have high serum glucocorticoid levels [30,44].…”
Section: Discussionmentioning
confidence: 99%
“…However, sustained elevations for long periods of time may have deleterious effects on different systems and thus lead to metabolic dysfunction, such as an increase in fat depots, insulin resistance, and dyslipidemia [42]. Some evidence indicates that anxiety disorders in rats are related to metabolic disturbances [6]. Human data also show a correlation between anxiety disorders and obesity [1,25].…”
Section: Introductionmentioning
confidence: 99%
“…In most cases, individuals with an avoidant coping style show metabolic diseases such as insulin resistance, metabolic syndrome, and obesity. This may indicate the existence of a connection between diseases and coping style (Boersma, Scheurink, Wielinga, Steimer & Benthem, 2009;Boersma, Benthem, van Dijk & Scheurink, 2011). In line with the above-mentioned psychological factors and their relation with food behaviour, Benard et al (2017) highlights the importance of impulsivity in the development of obesity.…”
Section: Introductionmentioning
confidence: 73%
“…Both response patterns can be considered as successful coping because they lead to shock avoidance. A positive correlation between shuttle box active avoidance and burying behavior in the defensive burying and a negative correlation between active avoidance and freezing behavior to the probe insertion were observed in the RLA/ RHA rat strains [142]. Furthermore, since both coping behaviors can be expressed within the task, the shock-probe burying paradigm is well suited to describe the neural circuitry of active and passive coping strategies.…”
Section: The Ecs As a Determinant Of The Types Of Fear Coping Strategiesmentioning
confidence: 99%